Energy Management System In Utility Grid Solar Cell And Battery For Power Stability - Ari Rahmawan, Novid; Effendy, Machmud; Nurhadi, Nurhadi (Frontier Energy System and Power Engineering, 2020)
A higher electric power generation was needed along with the increasing human populations and the development of technology. The use of renewable energy could act as an alternative way to solve the growing load demand. However, renewable energy faced an obstacle because electrical power could not be continuously built to fulfil the load’s requirement.  Transferring energy could help balance the energy and the system. Thus, the Energy Management System was needed to meet the stable and continuous load’s requirement. In this thesis, the Energy Management System was chosen as the scheduling system for DC’s grid with the PV as the renewable energy. The PV was connected on-grid to the utility network; thus, the power could be exchanged with the utility grid. A battery was used as the extra reserve energy supply when the highest loads happened. Based on the results, filling schedule of power was conducted by importing power when the load power requirement was less than 25 kW and no energy was generated from the PV. Furthermore, when there was power generation in the PV, the EMS would schedule the power at the incoming PV to meet the load when the generated power was higher than the required. The use of batteries as a backup energy source was utilised when the load requirement was greater than 25 kW because the battery here served to meet the power requirements when peak loads occur. The results also followed the EMS scheme, where the load’s demand was fulfilled entirely with precise scheduling. Finally, the strain on the DC bus was successfully maintained at 48 VDC to avoid energy decreasing.